Antiproliferative, apoptotic induction, and antiinvasive effects of Leersia hexandra (L.) Sw., Panicum repens Linn., and Brachiaria mutica (Forsk.) Stapf extracts on human cancer cells - Hansakul P. (2014)
In vitro study of antiproliferation and cytotoxicity of the hexane and butanolic extracts of the three grass species, namely Leersia hexandra (L.) Sw. ("Yaa sai"), Panicum repens Linn. ("Yaa channakaat"), and Brachiaria mutica (Forsk.) Stapf ("Yaa khon") demonstrated selective antiproliferative properties in both human lung cancer A549 and cervical cancer HeLa cell lines relative to normal human lung fibroblasts MRC-5, with significant differences in IC50 values (p<0.05). The butanolic extract of P. repens Linn. displayed the strongest growth inhibition in A549 and HeLa cells (IC50 2 and 1.1 mg/ml, respectively), whereas all other extracts exhibited only moderate to low antiproliferative effects (IC50 values, 90-980 mg/ml). Most grass extracts induced cell lethality at higher concentrations, suggesting their cytotoxic effects. The ELISA-based apoptosis assay showed that the hexane extract of these grasses triggered a significant increase in the level of apoptosis (p<0.05) in treated A549 cells. However, all the extracts induced ladder-like DNA fragmentation in both tumor cell lines in a dose- and time-dependent manner, suggesting that these extracts exhibit cytotoxicity through apoptotic induction. The study of anti-invasive effects of the three grass species revealed that the hexane extract of L. hexandra (L.) Sw. (50-100 μg/ml) and butanolic extract of P. repens Linn. (1 μg/ml) effectively reduced the invasive capacity of MDA-MB-231 cells.